Upaya Orang Tua dalam Meningkatkan Motivasi Belajar Siswa Kelas VII SMP Negeri 4 Biak Barat - Nasri Indra Padang (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This research is motivated by the lack of learning motivation among seventh-grade students at SMP Negeri 4 Biak Barat. The purpose of this study is to describe and analyze the efforts made by parents to increase the learning motivation of seventh-grade students at SMP Negeri 4 Biak Barat. Ten informants were interviewed, consisting of five parents and five seventh-grade students at SMP Negeri 4 Biak Barat. The data used were primary and secondary data. The data collection techniques used were non-participant observation, in-depth interviews, and document study. Data analysis consisted of data condensation, data presentation, and conclusion drawing. The results show that: parental efforts to increase learning motivation include several aspects, such as: (1) providing emotional support in the form of attention, affection, and understanding; (2) time management, parental presence during study time, playing with students during breaks; (3) appreciation and rewards, both verbal and material, as a form of positive reinforcement for student performance; and (4) facilities provided by parents at home, which are crucial factors in supporting student learning motivation.